2016
DOI: 10.3892/ol.2016.5138
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of long non-coding RNA profiles in human colorectal cancer and its association with overall survival

Abstract: Abstract. Long non-coding RNAs (lncRNAs) emerged as key regulators of diverse roles during colorectal cancer (CRC) carcinogenesis, but their specific function still remains to be explored. The present study aimed to re-annotate the Affymetrix Human Exon 1.0 ST Array for defining differential lncRNAs in CRC. Their prognostic relevance was also developed for screening key regulators in CRC. The CRC datasets E-GEOD-31737, E-MATB-829, Affymetrix colon cancer dataset and E-GEOD-24550 were re-purposed for searching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
5
29
0
Order By: Relevance
“…FAM83H-AS1 was consistently over expressed in breast tumor samples and overall survival analysis of TCGA data sets showed poor prognosis of the up regulated group which are in agreement with other studies in breast, colorectal and lung cancer (Lu et al, 2018;Yang et al, 2016a;Yang et al, 2016c;Zhang et al, 2017). Functional studies have demonstrated that knock-down of FAM83H-AS1 proliferative potential through MET/EGFR signaling in lung adenocarcinoma and NOTCH1 signaling pathway in colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…FAM83H-AS1 was consistently over expressed in breast tumor samples and overall survival analysis of TCGA data sets showed poor prognosis of the up regulated group which are in agreement with other studies in breast, colorectal and lung cancer (Lu et al, 2018;Yang et al, 2016a;Yang et al, 2016c;Zhang et al, 2017). Functional studies have demonstrated that knock-down of FAM83H-AS1 proliferative potential through MET/EGFR signaling in lung adenocarcinoma and NOTCH1 signaling pathway in colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…MYU is expressed in various tumors with a broad spectrum. MYU has been reported to regulate CRC based on its annotated sequence (14,15). However, its future application may be limited due to the lack of an accurate transcript.…”
Section: Discussionmentioning
confidence: 99%
“…A c-Myc-upregulated lncRNA MYU (ENSG00000261373) has been reported to exert an oncogenic effect in colorectal cancer (CRC) (14,15), but functions as a tumor-suppressor gene in gastric cancer (GC) (16). A recent study suggests that MYU as a target for Wnt/c-Myc signaling can promote cell cycle progression by stabilizing CDK6 expression via associating with hnRNP-K (14).…”
Section: Introductionmentioning
confidence: 99%
“…The 14 studies contained 2818 patients from three countries including China, United States and Iran. We mainly analyzed nine different types of tumors, including pancreatic ductal adenocarcinoma [13], gastric cancer [7,14,15], ovarian cancer [8,16], glioma [9], colorectal carcinoma [17,18], bladder cancer [10], hepatocellular carcinoma [6], breast cancer [19], and lung cancer [20]. The expression of FAM83H-AS1 was detected by quantitative real-time fluorescent PCR in all studies.…”
Section: Characteristics and Basic Information In Eligible Literaturementioning
confidence: 99%